EBV-Infection in Cardiac and Non-Cardiac Gastric Adenocarcinomas is Associated with Promoter Methylation of p16, p14 and APC, but not hMLH1 - Helene Geddert; Axel zur Hausen; Helmut E. Gabbert; Mario Sarbia (Analytical Cellular Pathology)
Background: Epstein–Barr virus (EBV)-associated gastric carcinomas (GC) constitute a distinct clinicopathological entity of gastric cancer. In order to determine underlying distinct aberrant promoter methylation we tested cardiac and non-cardiac GC with regard to the presence of EBV.